ANKLE-BRACHIAL INDEX AND LDL-RECEPTOR GENE IN ASYMPTOMATIC SEVERE HYPERCHOLESTEROLEMIA - L. Vladimirova-Kitova (Peytchinski Publishing, 2011)
The issue with the different levels of ankle-brachial index, as screening for LDL-receptor defective gene in newly detected asymptomatic severe hypercholesterolemia is less studied, but quite interesting. There have not been any studies on ankle-brachial index in patients with severe hypercholesterolemia in Bulgaria. Aim: To examine the difference between patients with severe hypercholesterolemia, who are carriers and non-carriers of LDL-R defective gene, with respect to their structural (ankle-brachial index) characteristics of arterial wall. Methods and materials: 60 patients with documented severe hypercholesterolemia >7.5 mmol/l satisfying the Simon-Broom criteria for clinically established and probable Familial Hypercholesterolemia were studied. All of the patients had a negative stress echocardiography and not known coronary artery disease. The laboratory used was the Clinical Laboratory at the Medical University Plovdiv. The total cholesterol and triglycerides were measured with enzyme-colorimetry and cholesterol in high density lipoprotein and cholesterol in low density lipoprotein with direct automatic analyses. Apolipoproteins were calculated by immunoturbodimetric method. The biochemical analyzer Konelab 60i was used in all the measurements. Results: According to whether there were or were not molecular defects, patients were assigned to two groups: carriers (11 patients, 18 %) and non-carriers (49 patients, 82 %).There was a statistically significant difference (p < 0.001) in the age distribution of patients, carriers and non-carriers of molecular defects. This conclusion was confirmed by the calculated mean age in both patient groups. The mean age of non-carriers was 48.20 ± 0.47 years, the mean age of carriers - 45.77 ± 0.36 years. There were no statistical differences in the sex distribution in the study sample (χ2 = 0.05; p > 0.05). We found no statistically significant difference between non-carriers and carriers with respect to body mass index (25.30 ± 0.40 vs 24.63 ± 0.45, respectively, t = 0.50; p > 0.05). There was not a statistically significant difference in levels of total cholesterol, triglycerides, HDL-cholesterol, LDL-cholesterol between carries (p>0.05). The cholesterol x years. score was significantly higher in the carries (440.36 ± 0.25 mmol-y/L), than in the non-carries (390.30 ± 0.07 mmol-y/L). We found a significantly lower ABI in the carriers vs. non-carriers (p<0.001) (Table 2). This significant difference was confirmed after adjustment for age and gender (p<0.05) Conclusion: The major findings of the present study are that ABI is significantly lower in carriers of the LDL-R defective gene vs. non-carriers.